Family support is not a risk factor of negative self-esteem in HIV/AIDS women - Jean Valeria; Surilena Surilena; Yanto Budiman; Samsuridjal Djauzi; Haridana Indah (Faculty of Medicine, Universitas Trisakti, 2015)
BACKGROUND Women with HIV/AIDS (WLWHA) have a complex psychosocial burden and a tendency to negative self-esteem, possibly resulting in mental and emotional problems. They need family support to deal with the HIV/AIDS infection and its psychosocial burden. The purpose of this study was to determine chacteristics of family support, self-esteem, and depression of WLWHA and the relationship between family support and self-esteem and depression. METHOD This was a cross-sectional study of 99 WLWHA infected through their husbands/partners, with no history of drug abuse. The data was taken by a consecutive sampling of two proportions test at Dharmais Cancer Hospital from November 2013 – January 2014. The instruments comprised a demographic questionnaire, the Rosenberg Self-Esteem questionnaire, the Hamilton Depression Rating Scale (HDRS), and a family support questionnaire. The data was analyzed by binary logistic regression. RESULTS There were 99 respondents with mean age of 36 years, of whom 44.4% were high school graduates, 54.5% unemployed, and 91.9% had HIV/ AIDS for more than a year. Binary logistic regression analysis showed no significant relationship between family support and self-esteem (p=0.700) and depression (p=0.396). Good family support has a protective effect of 1.3 times (OR=0.772; 95%CI: 0.138-3.770) towards increasing self-esteem, whereas poor family support increases the risk of depression 1.5 times (OR=1.477; 95%CI: 0.598-3.645) in WLWHA infected with HIV/AIDS from their husband/partner. CONCLUSIONS Good family support tend to have a protective effect towards increasing self-esteem, whereas poor family support increases the risk of depression in WLWHA infected with HIV/AIDS from their husband/partner.